Phosphorus Fluxes in a Temperate Forested Watershed: Canopy Leaching, Runoff Sources, and In-Stream Transformation - Sohrt, Jakob; Uhlig, David; Kaiser, Klaus; von Blanckenburg, Friedhelm; Siemens, Jan; Seeger, Stefan; Frick, Daniel A.; Krüger, Jaane; Lang, Friederike; Weiler, Markus (Frontiers in Forests and Global Change, 2019)
Declining foliar phosphorus (P) levels call increasing attention to the cycling of this element in temperate forests. We explored the fluxes of P in a temperate mixed deciduous forest ecosystem in six distinct hydrological compartments: Bulk precipitation and throughfall, soil water draining laterally from three different soil depths (0-15, 15-150, 150-320 cm below soil surface), groundwater, creek and spring discharge, which were sampled at daily to bi-weekly resolution from March 2015 to February 2016. Atmospheric P fluxes into the ecosystem were equally partitioned between wet and dry deposition. Approximately 10% of the foliar P stock was lost annually by foliar leaching during late summer. The concentrations of dissolved P in soil water from the forest floor and upper mineral topsoil followed a pronounced seasonal cycle with higher concentrations during the vegetation period. The concentrations of P dissolved in soil water decreased with increasing soil depth. Using an end member mixing analysis (EMMA) we found that P sources feeding the spring water were both soil water from greater depths or groundwater with season specific contributions. Atmospheric P fluxes into the ecosystem determined in this study and P-release from weathering reported for the research site were large enough to compensate P losses with runoff. This suggests that declining foliar P levels of forests are unlikely the result of a dwindling total P supply, but rather caused by tree nutrition imbalances or alternative stressors.